Significance of the pineal gland hormone melatonin in maintaining the health of women of reproductive age (a review) - M. V. Danilova; E. N. Usoltseva (Акушерство, гинекология и репродукция)
Introduction. Maintaining women's reproductive health is an important task that requires safe approaches based on the pathogenesis. More and more studies address the role of the pineal gland (epiphysis) hormone melatonin (МТ) in the functioning of the reproductive system, as well as the impact of МТ deficiency on the women’s health.Aim: to analyze and summarize the available literature about the role of the pineal gland hormone МТ in the pathogenesis of gynecological diseases in women of reproductive age (infertility, endometriosis, polycystic ovary syndrome, premenstrual syndrome), and also about the impact of МТ deficiency on the health of women working night shifts.Materials and methods. The relevant publications were searched in domestic (eLibrary, CyberLeninka.ru) and international (Pubmed, Cochrane Library) databases; we looked up the materials published in the recent 7 years. In our search, we prioritized the free access to full text articles. The selection of sources was limited to the period from 2012 to 2019.Results. МТ is involved in the development of follicles by causing the oocytes maturation, promoting the development of embryos, inhibiting the synthesis of steroids in the ovaries and, therefore, reducing the level of steroids in the blood. MT delays ovarian aging through a variety of mechanisms, including the antioxidant action, the maintenance of the due length of the telomere, the upregulated expression of the aging-related SIRT genes, and also the regulation of the ribosome functioning. As MT protects germ cells from oxidative stress, it is essential for normal ovulation, fertilization and further development of the embryo; this hormone has an impact on the duration of the woman's fertility and the onset of menopause. MT has a potential therapeutic effect on endometriosis. The oncostatic role of MT in hormone-dependent breast tumors has been described. Disruption of normal MT production during night shifts is associated with the risk of developing breast cancer in shift workers. MT deficiency leads to circadian desynchronosis and may cause both somatic disorders (metabolic syndrome, obesity, oncopathology) and neuroendocrine dysregulation of the female reproductive system.Conclusion. The variety of physiological functions of the pineal gland hormone MT emphasizes the pathogenetic role of its deficiency in many gynecological and somatic diseases. Of particular relevance is the increased risk of cardiovascular disorders, the development of metabolic syndrome and breast cancer in women who work night shifts. Therefore, it is important both to maintain normal endogenous level of MT and also use its therapeutic potential to maintain the health of women of reproductive age.